Studi Kekuatan Impact Laminasi Sistem Sisip (Sandwich) Fiberglass dan Polyurethane Foam - Okvani heys saputro; Akhmad Basuki Widodo (Fakultas Teknik, Universitas Bhayangkara Jakarta Raya, 2022)
Fiberglass boats are one of the options that are often used as an alternative to wooden boats. However, leaks on fiberglass boats are very difficult to handle at sea, so laminate using a sandwich system on fiberglass material and Polyurethane Foam can be a solution to deal with leaks on fiberglass boats at sea, where Polyurethane Foam can be a solution to prevent the entry of water when the fiberglass material experiences leaks or cracks in fiberglass boats. In this study, tests will be carried out on the laminated system of fiberglass inserts and polyurethane foam with variations of three types of polyol and isocyanate mixture compositions to form polyurethane foam materials, namely 1:1, 1:1.5, 1:2 using the charpy type impact test method with reference to on ASTM D256 93a to determine the impact value, then an analysis of the average value of the test results was carried out and compared with the impact value of fiberglass sandwich composites reinforced with palm fiber and epoxy. From the results of the impact test, the average 1:1 variance is 0.033j/cm3, and the 1:1.5 variance is 0.038j/cm3, 1:2 variance is 0.034j/cm3. From the test results, it was found that the average value of the variance of 1:1.5 was able to exceed the value of fiber composites reinforced with fibers and epoxy which had the same thickness on the skin.